O Trabalho Do Guincheiro No Porto De Vitória/Es E Os Desafios Do Processo Formativo (Global Journal of Human-Social Science, 2020)
This article analyzed the formative process of the Board Crane Driverin the port of Vitória/ES. It was used as methodological strategy the creation of a work analysis group as dispositive to data production. Through the analyzes, the production of a sensible bodyguincheiro in the work that emerges as a fundamental arbiter of the choices made, that carries the practical knowledge, incarnated, coming from the activity and that doesn't "subdue" to the simple execution or simulation of a task, either by repetition or protocols stipulated by the work organization in the port, but which places itself as the center of activity, the locus of rule debates.
Keywords: board crane driver; formation; port work